2021
DOI: 10.1039/d1qm00617g
|View full text |Cite
|
Sign up to set email alerts
|

Imogolite: a nanotubular aluminosilicate: synthesis, derivatives, analogues, and general and biological applications

Abstract: Imogolite is an aluminosilicate mineral originally found in volcanic ash derived soils. Through the use of chemical synthesis methods this mineral has been successfully synthesized and a number of modified...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 232 publications
0
6
0
Order By: Relevance
“…Recent works proposed several pathways (varying the concentration and the nature of the precursors, pH, and temperature) to obtain INTs with monodisperse diameter and chirality combined with controlled functionalization of the interfaces. [18][19][20] In particular, the isomorphic substitution of silicon by germanium allows obtaining INTs with either singlewalled (SW) or double-walled (DW) structures depending on the concentration of aluminum precursors (Figure 1). [21] D. Vantelon The progress in synthesis methods has brought new insights into the growth mechanism of INTs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works proposed several pathways (varying the concentration and the nature of the precursors, pH, and temperature) to obtain INTs with monodisperse diameter and chirality combined with controlled functionalization of the interfaces. [18][19][20] In particular, the isomorphic substitution of silicon by germanium allows obtaining INTs with either singlewalled (SW) or double-walled (DW) structures depending on the concentration of aluminum precursors (Figure 1). [21] D. Vantelon The progress in synthesis methods has brought new insights into the growth mechanism of INTs.…”
Section: Introductionmentioning
confidence: 99%
“…hydrophilic or hydrophobic surfaces). [15,16] Recently, density functional theory (DFT) studies suggested that INTs could be the ideal photocatalyst, offering at the same time high reactive surface area and natural charge carrier separation thanks to its permanent polarization. [17] The originality of these nanotubes stems from the atypical spatial separation of the valence (VB) and conduction band (CB) edges across the nanotube walls, [17][18][19] Such a unique VB/CB configuration should promote an efficient charge carriers separation of electrons and holes (e -/h + ), resulting in an enhanced photoefficiency by reducing e -/h + recombination.…”
Section: Introductionmentioning
confidence: 99%
“…This strain is a driving force for the 2D layer to roll into a nanotube. It has been shown that this class of materials, which includes imogolite 26 as well as TMD structures, form nanotubes with a preferred size, often in the nm range, which corresponds to the structure being energetically more favorable. 27…”
Section: Introductionmentioning
confidence: 99%
“…This strain is a driving force for the 2D layer to roll into a nanotube. It has been shown that this class of materials, which includes imogolite 26 as well as TMD structures, form nanotubes with a preferred size, often in the nm range, which corresponds to the structure being energetically more favorable. 27 In recent work, Mikkelsen and co-workers investigated the structural and electronic properties of single wall (SW) 1H-MoSTe nanotubes obtained by wrapping up Janus 2D sheets.…”
Section: Introductionmentioning
confidence: 99%